Evaluation tourism websites' usefulness and ease of use :a user's perspective - Bong, Sung Jong (Universiti Malaysia Sarawak, 2004)
For over the decade, the technology acceptance model (Davis, 1989) has been used to study user's intentions to adopt and use computing, technology.